PENERAPAN PRINSIP TANGGUNG JAWAB MUTLAK KEPADA PENANGGUNG JAWAB USAHA YANG MENIMBULKAN DAMPAK BESAR DAN PENTING TERIIADAP LINGKUNGAN HIDUP - Sutoyo Sutoyo (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2010)
Abstract: This article at knowing the parties that become the victims of the hot mud overflow, knowing the form and value of the loss, and investigating how far PT Lapindo Brantas and Bakie Group that is presumed as the causes the mud. This reasearch was conducted by qualitative approach. Conclusions is direct victims of the hot mud overflow mainly including most of Porong sub district, Tanggulanginand Jabon. While the indirect victims are all societies that used Gempol-Porong road access. The losses form of material and immaterial, the material losses about Rp ll,l trillion. The hot mud overflow of Sidoarjo has violated human right: wide society right for good and heatthy, environment, right for education, right for employment and good life, and violate property right of Sidoarjo populations. The hot mud overflow of Sidoarjo caused by the Banjarpanji I well drilling that is done by PT Lapindo Brantas.Then PT Lapindo Brantas and the Bakrie Group should responsible for the occurrence.